2019
DOI: 10.1021/acs.cgd.8b01636
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Synthesis of Low-Silica Nanozeolites through Geopolymer Chemistry

Abstract: Nanozeolites are of great interest with the premise of their efficiency in traditional applications such as catalysis and separation, as well as their emerging applications including chemical sensors, medicine, and food industry. We report a new geopolymerization route for the synthesis of nanozeolites with different crystal structures by exploring the Na−Al−Si−H 2 O quaternary phase space under a mild hydrothermal condition. Nanostructured faujasite (FAU), cancrinite (CAN), and sodalite (SOD) zeolites with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The synthetic zeolite used in this study, synthesized by our team through a “geopolymer gel” route, is a sodium aluminosilicate product containing Faujasite, Linda type A, and Sodalite frameworks for the precursor mixture compositions of Si/Al = 2 and Na/Al = 3 . The pure phase of Faujasite is obtained only in ratios of Si/Al = 3 and Na/Al = 4, which implies a narrow phase region for the structure . However, considering the large size of the pore openings in Faujasite nanozeolites and their high capacity as a carrier, we modeled a Faujasite-type zeolite for our DFT calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic zeolite used in this study, synthesized by our team through a “geopolymer gel” route, is a sodium aluminosilicate product containing Faujasite, Linda type A, and Sodalite frameworks for the precursor mixture compositions of Si/Al = 2 and Na/Al = 3 . The pure phase of Faujasite is obtained only in ratios of Si/Al = 3 and Na/Al = 4, which implies a narrow phase region for the structure . However, considering the large size of the pore openings in Faujasite nanozeolites and their high capacity as a carrier, we modeled a Faujasite-type zeolite for our DFT calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The research plan performed in this study is shown in Scheme . The zeolite model used in the DFT-D calculations is a Faujasite-type zeolite identified and characterized in a typical synthetic zeolite used in our study …”
Section: Introductionmentioning
confidence: 99%
“…17,18 In this study, nanozeolites are believed to be a promising carrier for large paraffin molecules due to nanozeolites' large external surface areas and large pore volumes. The scalable synthesis recently developed 19 makes nanozeolites more promising for further practical uses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of these unique features, nanozeolites have demonstrated an improved efficiency in their conventional catalysis, separation, and other emerging applications in areas such as medicine, antimicrobials, and the food industry. , In this study, nanozeolites are believed to be a promising carrier for large paraffin molecules due to nanozeolites’ large external surface areas and large pore volumes. The scalable synthesis recently developed makes nanozeolites more promising for further practical uses.…”
Section: Introductionmentioning
confidence: 99%
“…Liguori et al [15] obtained a self-supporting zeolitic material with a hierarchical porosity by combining zeolite crystallization with a foaming process initiated by silicon and found that the silicon content, the relative humidity and curing time had great effect on the nucleation and growth of zeolite phases. Chen et al [16] had successfully synthesized various low-silica nanozeolites including FAU, cancrinite (CAN), Linde-Type A (LTA), and sodalite (SOD) by exploring geopolymeric Na-Al-Si-H 2 O quaternary phase diagram. Compared to NaA(4.1 Å) and Na-P1(3.5 Å) [17,18], faujasite (FAU) has a characteristic pore size of 7.4 Å and a unique supercage structure, which is widely used in the field of heavy metal ion adsorption [19,20].…”
Section: Introductionmentioning
confidence: 99%